Plyometric, speed, and agility exercise prescription - Kovacs, M. (Conditioning for strength and human performance, 2013)
In most sports, athletes perform short (5- to 20-yd) or long (20- to 40-yd) sprints, change direction rapidly, or jump for height and/or distance. Therefore, linear acceleration and multidirectional speed; agility; and vertical, horizontal, and lateral jumping movements are essential elements of successful athletic performance. These locomotor skills are learned at young ages as children participate in unstructured playful activities. Maturation and experience will help refine the movement patterns associated with these skills; however, instruction on the mechanical aspects of locomotion is typically required to improve efficiency and performance and to limit the likelihood of injury. Once the global and segmental mechanical aspects of a skill have been mastered, training can focus on improving and ultimately maximizing performance. The types of exercises or drills prescribed to an athlete will be based on identified mechanical flaws or muscular weaknesses. To date, the manipulation of acute training variables for speed, agility, and plyometric training is unclear but will certainly depend on the athletic goals (short and long term), developmental stage, as well as chronological and training age.